A REVIEW ON THE THERAPEUTIC PROPERTIES OF TRICHOSANTHES CUCUMERINA LINN - Kavitha.S (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Trichosanthes cucumerina is an annual climber belonging to the family Cucurbitaceae, commonly known as snake gourd, viper gourd, snake tomato, or long tomato. The plant has been used traditionally for getting relief from headache, alopecia, fever, abdominal tumors, bilious, boils, acute colic, diarrhoea, haematuria and skin allergy. T. curcumeria is used as an vermifuge, abortifacient, haem agglutinant, refrigerant, laxative, purgative, emetic, bronchitis, cathartic and anthelmintic. The fruit of the plant is nutritionally rich and is commonly used as a vegetable. The potent pharmacological properties of the plant are mainly due to the presence of flavonoids, carotenoids, phenolic acids, and soluble and insoluble dietary fibers and essential minerals. T. cucumerina is reported to have many biological activities like anti HIV, cardioprotective, anti-ulcer, antidiabetic, hepatoprotective, anti inflammatory and larvicidal effects. The present review is aimed to highlight the various therapeutic properties of the plant in detail.